Um século de história: inventário do patrimônio cultural edificado do 29º GAC AP grupo humaitá no município de Cruz Alta/RS - Silva, Mateus Veronese Corrêa da (2015)
The architectural heritage of a place is not just the architectural elements expressed in its construction, but through memory, the historical burden and the daily experiences of the people involved in its existence. Thus, the government and the community in which this heritage is inserted, need to recognize its preservation as a means of safeguarding its history. At the same time, this expression is one of the most significant events for the understanding of urban history, so it is essential to carry out analyzes that reveal the cultural and constructive aspects arranged in its walls. Thus, this paper proposed to inventory the architectural ensemble of an example of the military heritage present in the city, built in 1909, Vigésimo Novo Grupo de Artilharia de Campanha Auto Propulsada, known by the nickname Grupo Humaitá. The research aims to highlight the historical, cultural and architectural aspects of the institution, emphasizing the analysis of the implementation and on the frontage of buildings, as a contribution to the pursuit of preservationist awareness. This information was cataloged by executors records as a way to contribute to the development of the inventory of military and civilian buildings of cultural interest in Cruz Alta and in Rio Grande do Sul. Through this work, it was intended to go along to enlarge the knowledge and dissemination of this property before the cruzaltense community, rescuing the memory, and providing subsidies to contribute to public policies and action plans in the areas of preservation of this heritage in the city as a way of disseminating the research, it was supposed to prepare a visual guide of the architectural repertoire of the buildings as a way to publicize the data and contribute to actions in favor of heritage education.